Wind turbine drive train dynamic characterization using vibration and torque signals. (April 2016) - Srikanth, P.; Sekhar, A.S.
Abstract: Dynamic analysis of wind turbine drive train subjected to stochastic aerodynamic loads is carried out in the present study. The longitudinal wind speed at the turbine site normally consists of a mean value superimposed with ramp, gust and turbulence components. In the present study, the aerodynamic torque is obtained by considering wind speed parameters of a typical wind turbine site. The dynamic model accounts for time varying gear mesh stiffness, bearing elasticity and torsional shaft stiffness. The dynamic analysis is done with stochastic aerodynamic loads and the vibration responses are obtained in time and frequency domains. It is observed that the entire spectral content of the vibration signals is confined to low frequency region, whereas higher frequencies are hidden. In order to capture the hidden frequency information from vibration signals, the wavelet decomposition technique is used. The dynamic analysis using torque signals is also discussed. The present study shows that, from the internal resistive torque all the characteristic frequencies can be clearly observed. Highlights: Turbulence in wind is modeled in detail to make the vibration signal realistic. The effect of rotational sampling on the dynamic response is clearly captured. The drive train dynamic characterization through torque signals is revealed. The procedure to measure internal resistive torque in gearbox is discussed. From the internal resistive torque characteristic frequencies are clearly observed.